The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ajh.26313
|View full text |Cite
|
Sign up to set email alerts
|

The impact of granulocyte colony stimulating factor on patients receiving chimeric antigen receptor T‐cell therapy

Abstract: Infectious complications following immunosuppressive therapy increase morbidity and mortality in patients combatting malignancy. 1 The inverse relationship between circulating leukocyte levels and infection potential places patients with prolonged and profound neutropenia at greatest infection risk. 2 Granulocyte colony stimulating factor (GCSF) after aggressive chemotherapy is a supportive measure recommended to reduce neutropenia intensity and ultimately abrogate infection.Chimeric antigen receptor T-cell (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 9 publications
(11 reference statements)
3
24
0
Order By: Relevance
“…Several retrospective studies have explored the effects of G-CSF on outcomes after CAR T in lymphoma. A group from Mayo Clinic compared 35 patients who received G-CSF after CAR T to 35 patients who did not—with no signal of increased severity of CRS or ICANS, and shorter duration of neutropenia with post-CAR T G-CSF [ 27 ]. Another study compared 42 patients who received G-CSF five days after CAR T to 28 G-CSF non-exposed patients, and found no difference in CRS or ICANS [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have explored the effects of G-CSF on outcomes after CAR T in lymphoma. A group from Mayo Clinic compared 35 patients who received G-CSF after CAR T to 35 patients who did not—with no signal of increased severity of CRS or ICANS, and shorter duration of neutropenia with post-CAR T G-CSF [ 27 ]. Another study compared 42 patients who received G-CSF five days after CAR T to 28 G-CSF non-exposed patients, and found no difference in CRS or ICANS [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were some concerns that G-CSF might affect CAR T-cell response or worsen CRS or ICANS via the activation of myeloid-related cytokines [77,78]. Overall, the data on the G-CSF are still conflicting, and some studies did not support this concern or suggested that G-CSF administration after the acute phase of CAR T-cell may shorten the duration of neutropenia and decrease the risk of infection in CAR T-cell recipients [79][80][81][82]. However, the finite role and effect of G-CSF require further studies.…”
Section: Antibacterial Prophylaxis: As Risk Of Bacterial Infectionmentioning
confidence: 99%
“…The incidence, severity, and duration of ICANS and utilization of tocilizumab and corticosteroids were similar between the two groups. 5…”
Section: To the Editormentioning
confidence: 99%
“…The incidence, severity, and duration of ICANS and utilization of tocilizumab and corticosteroids were similar between the two groups. 5 The immune impact of G-CSF on the repertoire and function of T cells have been explored previously. Earlier studies had demonstrated the impact of G-CSF-mobilized allografts on altering T-cell alloreactivity.…”
mentioning
confidence: 99%